A Comparative Study of the Attitudes of Freshman and Senior Nursing Students towards Nursing Discipline - MS Chehri; A Soori laki; A Ebadi; H Mahmoudi; MJ Sepahvand (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Students' attitudes towards their field of study can significantly affect the quality of education and their interest in learning and professional practice. The aim of this study was to compare freshman and senior nursing students' attitudes towards nursing.   Material & Methods: This cross-sectional descriptive study was conducted in 2011 on bachelor's nursing students of medical science universities in Tehran, Iran. A random sample of 248 students (137 freshmen and 111 seniors) was recruited. Data was gathered by a standardized and valid attitude assessment questionnaire. Differences between the two groups were determined Chi-square test using SPSS-PC (v. 14.0).   Results: The findings revealed that 54.01% of freshmen and 23.5% of senior nursing students had a positive attitude toward their discipline. There was a significant difference between the two groups regarding their attitude toward nursing (P < 0.001). Conclusion: Regarding the results, negative clinical experiences as well as inconsistencies between students' expectations and the realities of clinical nursing practice might have negatively affected senior nursing students' attitude towards their profession. Accordingly, identification and removing the factors that would negatively affect students' attitude towards nursing is recommended.